Platform-Driven Operations: Rethinking Supply Chain Dynamics in Affiliate-Based Digital Ecosystems - Ashari, Denny Rakhmad Widi; Waskita, Gautama Sastra; Bakti, Nurimansyah Setivia; Rizkaputra, Fergiawan Alfianto; Rahmawati, Desi (Journal of Development Research, 2026)
The rapid rise of TikTok Affiliate has transformed how businesses in emerging markets organize operations, yet little is known about its impact on supply chain practices in technically complex sectors. This study aims to explore how TikTok Affiliate marketing reshapes operational dynamics within Indonesia’s motorcycle spare parts ecosystem. Using a qualitative phenomenological design, data were collected through in-depth interviews with affiliators, SME owners, and consumers, complemented by document analysis and field observations. The findings reveal that algorithmic mediation drives unpredictable demand shifts, affiliators act as cultural mediators influencing customer engagement, and SMEs adopt agile, platform-responsive supply chain strategies. Trust and informal governance mechanisms emerged as crucial in sustaining operations, while infrastructural gaps highlight the challenges of digital integration in Indonesia. The study contributes to operations management literature by framing affiliate marketing as an operational phenomenon and provides practical insights for SMEs, policymakers, and digital ecosystem stakeholders.